Faktor-Faktor yang Mempengaruhi Pendapatan pada Usaha Tani Jagung di Desa Daenaa Kecamatan Limboto Barat Kabupaten Gorontalo - Afriyanto Saleh; Amir Halid; Mohammad Zubair Hippy (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This study aims to determine the effect of production factors on income in corn farming. This study falls within the descriptive quantitative approach category of survey research. Both primary and secondary data types are utilized. In order to get a sample of 51 corn farmers, the sampling technique employed is a systematic sampling of the population of 819 corn farmers. Multiple linear regression analysis is the data analysis method used. The findings revealed that According to a significant value of 0.000, the independent variables of land area, labor, seeds, fertilizer, pesticides, and agricultural machinery all have a tangible impact on the dependent variable of farmer income when taken together (simultaneously). Second, five independent variables have a genuine (significant) impact on the dependent income variable: land area, labor, seeds, fertilizer, and pesticides. In contrast, agricultural machinery has no influence (insignificant) on income. Third, the coefficient of determination (R2) of 0.823 indicates that the independent variables under investigation account for 82.3% of the revenue, while production factors unrelated to the dependent variables account for 17.7%.